2013
DOI: 10.1177/1934578x1300801117
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Extracts and Fractions from Aerial Parts of Selected Plants (Garcinia achachairu, Macrosiphonia velame, Rubus niveus and Pilea microphylla) Against Some Pathogenic Microorganisms

Abstract: As part of the program of our research group to search for new and effective substances from the Brazilian biodiversity, the present work evaluates the antibacterial activity of four species from the Brazilian flora (Garcinia achachairu, Macrosiphonia velame, Rubus niveus and Pilea microphylla) against Bacillus subtilis, Staphylococcus aureus and S. saprophyticus (Gram-positive bacteria), Escherichia coli (Gram-negative bacterium) and Candida albicans (yeast). The extracts of R. niveus and M. velame showed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Also referred to as “achachairu”, this evergreen tree belongs to the Clusiaceae family and has been traditionally utilized by indigenous communities for its medicinal benefits. Preparations obtained from different parts of this plant have already been the subject of studies revealing antimicrobial [ 15 ], gastroprotective [ 16 ], anti-inflammatory [ 17 ], and diuretic [ 18 ] properties. In the present study, we extended these actions to understand the benefits of this plant in mechanisms that contribute to the control of blood pressure, since the demonstration of diuretic activity has already opened this promising perspective.…”
Section: Resultsmentioning
confidence: 99%
“…Also referred to as “achachairu”, this evergreen tree belongs to the Clusiaceae family and has been traditionally utilized by indigenous communities for its medicinal benefits. Preparations obtained from different parts of this plant have already been the subject of studies revealing antimicrobial [ 15 ], gastroprotective [ 16 ], anti-inflammatory [ 17 ], and diuretic [ 18 ] properties. In the present study, we extended these actions to understand the benefits of this plant in mechanisms that contribute to the control of blood pressure, since the demonstration of diuretic activity has already opened this promising perspective.…”
Section: Resultsmentioning
confidence: 99%
“…An examination of the group of studies identified using the search terms Garcinia humilis and achachairu revealed that Guttiferone A was the predominant compound identified in the seed of the fruit (Niero et al, 2012). The studies highlighted that the raw methanolic extract and the pure compound (Guttiferone A) exhibit a rich medicinal profile, showing antinociceptive and gastroprotective properties with antileishmanial and antimicrobial activities (Dal Molin et al, 2012;Cechinel-Filho et al, 2013;Melim et al, 2013), low genotoxicity (Marques et al, 2012), analgesic properties (Terrazas et al, 2013), effects against certain models of induced ulcers and reduction of gastric secretion (Niero et al, 2012), in addition to pronounced antiproliferative activity against cell lines, revealing potential anticancer activity (Mariano et al, 2015).…”
Section: Categories Of Publication and Review Of The Main Resultsmentioning
confidence: 99%
“…Root is also used for the treatment of dysentery and diarrhea (Pfoze et al, 2012). Chemical and pharmacological studies have shown that products from aerial parts and some extracts have nematicidal activity (Sultana et al, 2010); antimicrobial activity of extracts and fractions from aerial parts Melin et al (2013); and root extract have anti-inflammatory, analgesic, antipyretic (George et al, 2013), antitumor and wound healing properties (George et al, 2014).…”
Section: Introductionmentioning
confidence: 99%